MEDIA PEMBELAJARAN PAI DI ERA DIGITAL - Anis Nirmala Patmawati; Inayah Rahmayani Mutmainnah; Shinta Adha Selina; Silvia Rahayu; Rachel Amalia; Azizurahman; Natasya Amelia Loviana; Sabrun Jamil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of digital technology in the era of the Industrial Revolution 4.0 and Society 5.0 has significantly influenced the implementation of Islamic Religious Education (PAI). Conventional learning approaches are no longer sufficient to meet the characteristics of Generation Z and Alpha students who are closely connected to digital media. This study aims to examine the forms of digital learning media used in PAI and their roles in supporting students’ motivation, engagement, and understanding. This research employs a qualitative descriptive approach through library research by reviewing relevant academic journals and scholarly books. The analysis focuses on identifying dominant types of digital media, their educational benefits, and the challenges faced in their implementation. The findings indicate that interactive multimedia, video-based learning, gamification, and immersive technologies help students understand abstract Islamic concepts more concretely and encourage active participation in learning. However, the effectiveness of digital learning media is highly dependent on teachers’ pedagogical readiness, digital competence, and supporting infrastructure. Therefore, thoughtful integration and continuous teacher development are essential to ensure meaningful and value-based PAI learning in the digital era.